2015
DOI: 10.17660/actahortic.2015.1068.18
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Predicting Diameter of 'Red Sensation' Pears

Abstract: The pear cultivar 'Red Sensation' is showing popularity in the industry, because of its highly-colored, sweet and juicy fruit. Fruit size is critical for marketing pear; therefore, knowledge of growth dynamics becomes essential to program harvesting with minimum losses of size and flavor. The objective of this work was to develop a model to predict the seasonal growth for 'Red Sensation' pears, expressed in terms of fruit diameter as a function of time from full bloom. Fruit growth was followed at the Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Similar to the diameter growth in fruits of the 'Red Sensation' pear tree [38] and in fruits of Asian pear trees [39], the equatorial diameter growth of the fruit in the present study during the two years showed a behavior adjusted to a sigmoid logistic model, defined in three phases. In the first phase, cell division occurred from flowering up to 49 and 50 days after flowering (DAF) in 2014 and 2015, respectively, with rapid growth.…”
Section: Production Parameterssupporting
confidence: 75%
See 1 more Smart Citation
“…Similar to the diameter growth in fruits of the 'Red Sensation' pear tree [38] and in fruits of Asian pear trees [39], the equatorial diameter growth of the fruit in the present study during the two years showed a behavior adjusted to a sigmoid logistic model, defined in three phases. In the first phase, cell division occurred from flowering up to 49 and 50 days after flowering (DAF) in 2014 and 2015, respectively, with rapid growth.…”
Section: Production Parameterssupporting
confidence: 75%
“…The third phase, in which maturation was reached, was characterized by a continuous increase in diameter from 113 and 114 DAF until harvest (169 and 161 DAF) for 2014 and 2015, respectively (Figure 1A,B), which concurred with reports for pear [37] and apricot [40] plantations. Similarly, Garriz et al [38] found that the maximum value for the AGR of the fruit was 0.61 mm day −1 . In addition, those authors determined three phases of growth in the diameter of the fruits, whose growth curve had a sigmoid shape.…”
Section: Production Parametersmentioning
confidence: 76%